MEKANISME AKREDITASI SEKOLAH/MADRASAH DALAM PENJAMINAN MUTU PENDIDIKAN YANG BERKELANJUTAN - Alfisyah; Misda Ariyani; Husnul Yaqin; Hilmi Mizani (PT. Hasba Edukasi Mandiri, 2026)
This study aims to provide a comprehensive understanding of the school/madrasah accreditation mechanism, covering its basic concepts, stages and procedures, as well as the implementation and follow-up of accreditation results in an effort to improve the quality of education. This study employs a literature review method, examining various written sources such as legislation, accreditation guidelines, books, and relevant previous research findings. Data collection was carried out through documentary study using a text analysis approach, whilst data analysis employed content analysis to identify and categorise information related to the accreditation mechanism. The research findings indicate that accreditation functions not only as an administrative evaluation tool but also as an instrument for quality assurance and development in education through a systematic and continuous evaluation process. However, various challenges remain in its implementation, such as limited understanding of accreditation instruments, an administrative bias, and the suboptimal utilisation of accreditation results within the internal quality assurance system. Therefore, a comprehensive understanding and appropriate strategies are required to ensure that accreditation functions optimally as a means of improving the quality of education.